Participatory Value Evaluation: a novel method to evaluate future urban mobility investments - Niek Mouter; Paul Koster; Thijs Dekker (Tinbergen Institute, 2019)
Cost-Benefit Analysis (CBA) is a widely applied economic appraisal tool to support the planning and decision-making process for transport projects. However, in the planning literature CBA has been criticized for at least three reasons: 1) CBA focuses on traditional transport system related planning goals and poorly considers the broader goals of urban transport planning such as social equity; 2) CBA corrodes and degrades the forward looking nature of the planning proficiency. The instrument can be conceived as a backward looking methodology as it assumes that people's past decisions in a (private) market setting reflect their normative ideas regarding their preferred future urban mobility system; 3) CBA fails to recognize the specific (local) features of the problem which a transport project aspires to solve as practical CBA studies use generic price tags to value impacts of a transport project. Participatory Value Evaluation (PVE) is a novel evaluation approach specifically designed to overcome these criticisms while preserving the positive aspects that CBA brings to planning. This paper illustrates the PVE method with a case study on the evaluation of a transport investment scheme of the Transport Authority Amsterdam. In total 2,498 citizens participated in the PVE. We find that projects with the highest social value focus on safety and improvements for cyclists and pedestrians, whereas projects that focus on reducing travel times for car users have lower value. Moreover, we establish that PVE captures citizens' preferences towards broader goals of transport planning such as improving health and the environment, fostering city cycling as well as the inclusion of ethical considerations such as spatial equality. PVE also allows for the inclusion of citizens' normative ideas regarding their preferred future urban mobility system and local characteristics of the transport problem/solution.
Keywords: O21; D61; D63; R42; R58; 330